EDITORIAL - Palhano Ricarte Oliveira, Angelo; Leiros Sarmento da Silva, Iasmin; Chaia, Jade Oliveira; Rodrigues Rocha, Maria Clara; Alves Teixeira, Michelly; de Souza Maciel, Verônica; Rossinetti Rufinoni, Priscila (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2018)
Editorial do número 06, volume 12, ano 2017.